Competence, Reporting, and Accessibility in Village Financial Management Accountability: Kompetensi, Pelaporan, dan Aksesibilitas dalam Akuntabilitas Pengelolaan Keuangan Desa - Ningrum, Ravika Sevtia; Nurasik , Nurasik (Indonesian Journal of Law and Economics Review, 2024)
Accountability in village financial management is vital for promoting transparency and good governance at the local level. Despite its importance, there is limited understanding of how the competence of village officials, the presentation of financial reports, and the accessibility of these reports contribute to achieving financial accountability. This study addresses this knowledge gap by exploring the relationship between these factors and the accountability of village fund management in Krembung District, Sidoarjo Regency. Utilizing a quantitative approach, primary data were gathered through questionnaires from a purposive sample of 57 respondents across 19 villages. The data were analyzed using multiple linear regression with SPSS version 23. The findings indicate that the competence of village officials, the presentation of village financial reports, and their accessibility all have a positive and significant effect on the accountability of village financial management. The novelty of this research lies in its combined analysis of these three factors within a village context, providing comprehensive insights into enhancing financial accountability. Implications suggest that improving the skillset of village officials and financial reporting practices is essential to fostering better financial accountability at the village level. Highlights: Positive Effect: Competency, report presentation, and accessibility boost financial accountability. Quantitative Analysis: Study used questionnaires and multiple linear regression. Key Insight: Improving officials' skills and reporting practices enhances accountability. Keywords: Accountability, Village Financial Management, Competency, Financial Report Presentation, Accessibility